A systematic analysis of the Polish Code of Medical Ethics - Anna Augustynowicz; Adam Skowron; Michał Waszkiewicz; Mateusz Eid; Janusz Sytnik-Czetwertyński (Kazimierz Wielki University, 2019)
The purpose of this article is to provide a summary of the history which led to the creation of the current structure of the self-regulatory professional body of physicians and dentists, the nature of the professional activities and practice of physicians, as well as an analysis of the legal basis for the adoption of the Code of Medical Ethics. This allows us to draw a series of conclusions as to the influence of the existence of the professional self-regulatory body of physicians on the functioning of the Polish health service.